2003
DOI: 10.1136/gut.52.10.1408
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori upregulates matrilysin (MMP-7) in epithelial cells in vivo and in vitro in a Cag dependent manner

Abstract: Background and aims: Matrix metalloproteinase-7 (MMP-7) is important in normal and pathological remodelling of epithelial-matrix interactions, and is upregulated in gastric cancer. Helicobacter pylori infection is the first stage in gastric carcinogenesis, and therefore our aim was to determine if H pylori upregulated gastric MMP-7 expression and if this was affected by strain virulence. Methods: We took gastric biopsy specimens at endoscopy from H pylori infected (n = 17) and uninfected (n = 18) patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 45 publications
3
69
2
2
Order By: Relevance
“…Altered expression was found for several protease inhibitors, such as antithrombin III, serine protease inhibitor (Kazal type I), alpha-1-antitrypsin, and matrix metalloproteinase 3 (MMP-3) (all decreased) and MMP-15 (increased) (Tables 1 to 3). These results differ somewhat from recent studies using cultured gastric epithelial cells that demonstrated increased expression of proteases and protease inhibitors, such as MMP-1, -2, -3, -7, and -9 and ADAM (a disintegrin and metalloproteinase)-10 and -17 in gastric epithelial cells (9,10,24,38,48,63,99). Our results may emphasize differences between gene expression in cultured cells and an experimental animal model associated with H. pylori infection.…”
Section: Resultscontrasting
confidence: 56%
“…Altered expression was found for several protease inhibitors, such as antithrombin III, serine protease inhibitor (Kazal type I), alpha-1-antitrypsin, and matrix metalloproteinase 3 (MMP-3) (all decreased) and MMP-15 (increased) (Tables 1 to 3). These results differ somewhat from recent studies using cultured gastric epithelial cells that demonstrated increased expression of proteases and protease inhibitors, such as MMP-1, -2, -3, -7, and -9 and ADAM (a disintegrin and metalloproteinase)-10 and -17 in gastric epithelial cells (9,10,24,38,48,63,99). Our results may emphasize differences between gene expression in cultured cells and an experimental animal model associated with H. pylori infection.…”
Section: Resultscontrasting
confidence: 56%
“…In Hp-infected mucosa, epithelial cells appear to be one of the major sources of MMPs (19,20). Although Hp by itself can induce gastric epithelial cells to release MMPs (21,22), accumulating evidence indicates that cytokines produced by mucosal T cells and macrophages are also major stimuli for MMP production (16,23,24).…”
Section: Nfection By Helicobacter Pylori (Hp)mentioning
confidence: 99%
“…So it could be deduced that MMP-7 might participate in the penetration of BM and ECM in gastric carcinomas instead of promoting cell proliferation. Recently, two studies demonstrated that MMP-7 upregulation was closely related with the H pylori cag pathogenicity island and this implied a certain role of MMP-7 in carcinogenesis of gastric carcinomas [35,36] . Invasion and metastasis of gastric carcinomas are a multistep process.…”
Section: A B C D E Fmentioning
confidence: 99%